Exploration of the potential of genomic editing in the treatment of congenital adrenal hyperplasia - Graves, Lara E.; Christina, Sharntie; Mullany, Kathryn L.; Alexander, Ian E.; Falhammar, Henrik (Frontiers in Endocrinology, 2025)
Despite life-saving glucocorticoids, therapeutic options for congenital adrenal hyperplasia (CAH) remain sub-optimal. Adrenal crisis continues to be the highest cause of mortality in individuals with CAH and even with recommended treatment regimens complications from the disease and treatments themselves persist. These patients have limited treatment options and advanced therapeutics could be a solution. Development of genetic therapies have exponentially increased in recent years. The advent of CRISPR/Cas technology has brought previously inconceivable treatment options to reality. Genomic editing could repair the defective 21-hydroxylase gene and provide a cure for 21-hydroxylase deficiency, the most common CAH variant, eliminating the current need for constant patient intervention. There are a number of technologies within reach for CAH, however, delivery of the genomic editing reagents to the elusive adrenocortical progenitor cells remains challenging. Here we discuss the complexity of CAH genetics, which has implications for choice of genomic editing strategy, and potential future strategies for the development of a cure of CAH.